2008
DOI: 10.1248/bpb.31.651
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Corosolic Acid Ameliorates Obesity and Hepatic Steatosis in KK-Ay Mice

Abstract: Banaba leaves (Lagerstroemia speciosa LINN.) have been used as a traditional medicine in Southeast Asia, and tea made from the leaves is used as a treatment for diabetes. The leaves contain large amounts of corosolic acid (CRA) (Fig. 1), which recently has attracted attention for its biological properties. [1][2][3][4][5][6][7] It was shown that Banaba leaf extract (1% CRA) treatment for 2 weeks decreased blood glucose levels in humans. 8) In addition, CRA (10 mg) has been shown to reduce post challenge plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…6,12,13) Several studies in small rodents have reported that DPP IV inhibitors improved oral glucose tolerance in high-fat diet-fed animals. 6,11) Moreover, it has been confirmed that high-fat dietinduced insulin resistance and glucose intolerance were less prevalent in DPP IV-deficient rats than wild-type rats.…”
mentioning
confidence: 99%
“…6,12,13) Several studies in small rodents have reported that DPP IV inhibitors improved oral glucose tolerance in high-fat diet-fed animals. 6,11) Moreover, it has been confirmed that high-fat dietinduced insulin resistance and glucose intolerance were less prevalent in DPP IV-deficient rats than wild-type rats.…”
mentioning
confidence: 99%
“…Two kinds of specific diet were prepared for this study. One was a high cholesterol diet made of CE-2 (Clea, Japan), 1% cholesterol and 0.5% cholic acid, while the other was the same high cholesterol diet containing 0.023% CA, a dosage similar to that used in previous studies (22,30).…”
Section: Methodsmentioning
confidence: 99%
“…The hypoglycemic effect of CA has been noted in various experiments (7,14,22,25,29). In addition to the hypoglycemic effect, Yamaguchi et al reported its lowering effect on serum fatty acids in SHR/NDmcr-cp rats (31), while Yamada et al observed that CA reduced fasting plasma and liver triglyceride contents in KK-Ay mice (30). The occurrence of hyperlipidemia is prevalent in more than 30% of all diabetics, two to three times more frequent than in nondiabetic patients (1).…”
mentioning
confidence: 97%
“…Since GOAT recognizes fatty acyl-coenzyme (Co)A molecules, such as octanoyl-, hexanoyl-, and decanoyl-CoA [43], we speculated that the carboxyl group in a molecule is an important functional group for this inhibitory effect. Triterpenes, such as asiatic acid, betulinic acid, corosolic acid, glycyrrhetinic acid, oleanolic acid, and ursolic acid have shown antiobesity effects in mice fed a high-fat diet [44][45][46][47][48][49]. Like fatty acids, these triterpenes also have a carboxyl group in their structure, suggesting that they could also suppress octanoylated ghrelin production.…”
Section: Effects Of Triterpenes Contained In E Japonica Leaves On Ghmentioning
confidence: 99%